Avaliação do efeito de particulados sólidos na eficiência de um inibidor de corrosão recomendado para meios salinos com CO2 - Távora, Michele Portela (2007)
The main problem on the exploration activity on petroleum industry is the formation water resulted on the fields producing. The aggravating of this problem is correlated with the advancing technologies used on the petroleum extractions and on its secondary approach objecting the reobtainment of this oil. Among the main contaminants of the water formation are corrosives gases such as: O2, CO2 and H2S, some solids in suspension and dissolved salts. Concerning to those gases the CO2 is the one that produce significant damage for carbon steel on corrosion process of the petroleum and gas industries. Corrosion inhibitors for carbon steel in formation water is one of the most used agents in control of those damages. In this context, the poor investigations of carbon steel corrosion proceeding from solids in suspension is an opened field for studies. On this work the inhibitor effect of the commercial CORRTREAT 703 was evaluated on some specific solids in suspension at saline medium containing 10.000 ppm of de-aerated chloride using CO2 until non oxygen atmosphere been present. For that, quartz, calcium carbonate, magnetite and iron sulphide were subjected to this investigation as the selected solids. The effect of this inhibitor on corrosion process correlated with those specific solids, was measured using electrochemical (resistance of linear polarization and galvanic pair) and gravimetrical techniques. During all the experimental work important parameters were monitored such as: pH, dissolved oxygen, temperature, instantaneous corrosion rate and galvanic current. According to the obtained results it was proved that the suspension solids calcium carbonate and iron sulphide decrease the corrosion process in higher pH medium. Meanwhile the quartz and magnetite been hardness increase corrosion by broking of the passive layer for erosion. In the other hand, the tested inhibitor in concentration of 50 ppm, showed to be effective (91%) in this corrosion process